Pengaruh Customers Experience dan Customers Satisfaction terhadap Pembelian Ulang Produk Avoskin : - Berliana Putri Damayanti; Nurhadi Nurhadi (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This research is motivated by the conditions of competitive competition and the development of an advanced business sector that encourages companies to compete increasingly fiercely. Thus the company is required to provide satisfactory service to consumers. The purpose of this study was to determine and analyze the effect of Customers Experience and Customers Satisfaction on Repeat Purchase Avoskin products at @ohmybeautybank Followers. This study uses a test tool in the form of IBM SPSS Statistic 26. The population used is Followers Autobase @ohmybeautybank. The data collection used in this research is using a questionnaire. Data analysis in this study used descriptive statistical techniques. The results of the t-test indicate that Customers Experience and Customer Satisfaction have a positive effect on Repeat Purchase Avoskin products at @ohmybeautybank Followers where customers experience has a t-count of 3.250 while Customers Satification has a t-count of 2.123. So it can be concluded that Customers Experience influences Repeat Purchase more than Customers Satisfaction. Keywords: Customers Experience, Customers Satisfication, Repeat Purchase